2014
DOI: 10.1021/jo501958d
|View full text |Cite
|
Sign up to set email alerts
|

Regio- and Stereoselective Monoepoxidation of Dienes using Methyltrioxorhenium: Synthesis of Allylic Epoxides

Abstract: Methyltrioxorhenium (MTO) complexed with pyridine was shown to be a highly effective catalyst for the regioselective monoepoxidation of conjugated di- and trienes using 30% H2O2 at or below room temperature. The resultant allylic epoxides, and the triols derived from them, are versatile synthetic intermediates as well as substructures present in many bioactive natural products. The site of epoxidation was dependent upon olefin substitution, olefin geometry (Z vs E), and the presence of electron-withdrawing sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…The POM as a powerful catalyst has an excellent performance for the selective oxidation in organic reactions. With the deepening of the PONb research, scientists have reported some PONbs as organic reaction catalysts. , Compared with other POMs, there is still a large space for the catalysis study of PONbs. For a long time, the oxidation of olefins has been an important process due to the demand of the epoxides in the chemical industry. Here, we take compounds 1 – 3 as the catalysts to test their catalytic ability for the oxidation of styrene. The experimental epoxidations of styrene to styrene oxide were conducted in a batch reactor using aqueous tert -butyl hydroperoxide (TBHP) as the oxidant and compounds 1 – 3 as the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…The POM as a powerful catalyst has an excellent performance for the selective oxidation in organic reactions. With the deepening of the PONb research, scientists have reported some PONbs as organic reaction catalysts. , Compared with other POMs, there is still a large space for the catalysis study of PONbs. For a long time, the oxidation of olefins has been an important process due to the demand of the epoxides in the chemical industry. Here, we take compounds 1 – 3 as the catalysts to test their catalytic ability for the oxidation of styrene. The experimental epoxidations of styrene to styrene oxide were conducted in a batch reactor using aqueous tert -butyl hydroperoxide (TBHP) as the oxidant and compounds 1 – 3 as the catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…MTO-catalyzed highly regio-and stereoselective monoepoxidation of dienyl acetates, as well as conjugated diene and trienes, were developed by Falck et al in 2014 (Scheme 23). 47 Out of a series of catalysts and ligands, 5 mol% MTO in combination with 30% aq. H 2 O 2 (2 equiv.)…”
Section: Aqueous H 2 O 2 -Mediated Epoxidation Of Alkenesmentioning
confidence: 99%
“…The epoxidation of olefins is an industrially important process since epoxides are widely used as key intermediates in organic synthesis [1][2][3]. Recently, considerable interests have been drawn on studying the aerobic epoxidation of olefins for developing more efficient and environmentally benign route [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%